Male sterile mutant casanova gives clues to mechanisms of sperm-egg interactions in Drosophila melanogaster. - Perotti, M.E.; Cattaneo, F.; Pasini, M.E.; Verni, F.; Hackstein, J.H.P. (Molecular Reproduction and Development, 2001)
The plasma membrane of the spermatozoa of Drosophila melanogaster contains two integral proteins with glycosidase activity, beta-N-acetylglucosaminidase and alpha-D-mannosidase. Biochemical analysis and ultrastructural cytochemistry of spermatozoa of the autosomal male sterile mutant casanova reveal that at least one of these enzymes, beta-N-acetylglucosaminidase, is crucial for sperm-egg interactions. casanova sperm are motile, morphologically normal, are transferred to the female at mating, but are unable to fertilize the eggs. The mutation was localised by deficiency mapping to the chromosomal region 95E8-F7. Fluorimetric assays showed that the mutant's sperm have the same level of alpha-D-mannosidase activity as wild-type sperm, whereas beta-N-acetylglucosaminidase activity reaches only 51% of the wild-type level. The biochemical characteristics of alpha-D-mannosidase and of the residual beta-N-acetylglucosaminidase are the same as in wild-type males. Ultrastructural localization of the enzymes indicated that casanova spermatozoa lacks beta-N-acetylglucosaminidase on the plasma membrane covering the acrosome, whereas the location of this glycosidase at the terminal part of the sperm tail is indistinguishable from the wild-type situation. The results strongly suggest that in Drosophila the beta-N-acetylglucosaminidase of the plasma membrane covering the acrosome functions as a receptor for the glycoconjugates on the egg surface. We named the putative egg receptor EROS. This is the first evidence for an egg/sperm recognition system in insects. The mechanism is similar to those known from higher animals.